2009
DOI: 10.1016/j.bbmt.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Hematopoietic Stem Cell Transplantation May Reverse Renal Failure in Patients with Multiple Myeloma

Abstract: Approximately 20% of patients with multiple myeloma (MM) have renal failure at diagnosis, and about 5% are dialysis-dependent. Many of these patients are considered ineligible for autologous hematopoietic stem cell transplantation (auto-HSCT) because of a high risk of treatment-related toxicity. We evaluated the outcome of 46 patient with MM and renal failure, defined as serum creatinine >2 mg/dL sustained for >1 month before the start of preparative regimen. Patients received auto-HSCT at our institution betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 21 publications
4
80
0
3
Order By: Relevance
“…[19][20][21] Conversely, Parikh et al 22 evaluated outcomes of 46 patients with MM and renal failure and showed that MEL200 was not associated with increased toxicity and renal function improved in 32% of patients. Despite these conflicting data, major working groups such as IMWG and ABSMT recommend reducing the dose from 200 to 100-140 mg/m 2 in patients with CrCl o 60 mL/min based on decreased tolerability in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Conversely, Parikh et al 22 evaluated outcomes of 46 patients with MM and renal failure and showed that MEL200 was not associated with increased toxicity and renal function improved in 32% of patients. Despite these conflicting data, major working groups such as IMWG and ABSMT recommend reducing the dose from 200 to 100-140 mg/m 2 in patients with CrCl o 60 mL/min based on decreased tolerability in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Median time to neutrophil engraftment was 10 (range 7-12) and 9 (range 8-13) days in patients with CrCl o 60 mL/min and ⩾ 60 mL/min, respectively (P = 0.008). Median time to platelet engraftment was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)) and 10 (8-18) days in each group, respectively (P o 0.001). The median duration of hospitalization was significantly longer in patients with RI (14 (range 12-36) versus 16 (range 11-47) days, P = 0.02).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Studies on patients with renal dysfunction undergoing ASCT include only a small subset of patients on dialysis. 8,10,[12][13][14] It is encouraging, however, that even in patients with severe renal failure, improvements in renal function following transplantation can be observed. 9,[15][16][17] Unfortunately, patients with renal failure appear to have higher rates of treatment-related toxicities and transplantrelated mortality (TRM) compared with patients without renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Approximately 20-40% percent of patients with MM have renal impairment at the time of diagnosis and up to 2-3% of patients will require dialysis during their disease course. [4][5][6][7] Although ASCT appears feasible and safe in patients with mild to moderate renal impairment, [8][9][10][11] there are limited data in those with dialysis-dependent renal failure. Studies on patients with renal dysfunction undergoing ASCT include only a small subset of patients on dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In fact, several manuscripts reported the finding of some patients achieving hemodialysis independence after autologous HCT. 15,18,19 Variables predicting recovery from hemodialysis included requiring dialysis for o6 months prior to undertaking autologous HCT, attainment of complete CR or near-CR and creatinine clearance at time of autologous HCT 410 mL/min.…”
Section: Scope Of the Problemmentioning
confidence: 99%